Improved search method for classified reusable components on cloud computing - Rawashdeh, Adnan; Alkasassbeh, Mouhammd; Dwairi, Radwan; Abu-Salem, Hani; Al-Mattarneh, Hashem (Institute of Advanced Engineering and Science, 2024)
Expanding development environments to accommodate huge amounts of reusable components along with associated maintenance and evolution responsibilities has become difficult and costly for software organizations to cope with, while benefits are limited to owner organizations. The challenge of organizing reusable assets so that finding the right component needed has always been a big challenge. The literature of software reuse lacks a comprehensive search method that is efficient and covers the entire system development lifecycle (SDLC). This research work attempts to make an efficient use of the cloud computing advantages and thus, encourages the migration of reusable components to the clouds. The maintenance, the search process and cost-related problems encountered with traditional in-house development environments can be resolved conclusively on the cloud. This research work proposes a multi-classification and clusters approach to migrate reusable components to the cloud. Accordingly, it applies indexing process to classified reusable components achieving efficient search. In addition, the proposed approach adopts a comprehensive SDLC-based classification to organize reusable components so that searching and finding an appropriate component becomes an easy task due to the fact it is bound to the particular undergoing phase. Cloud computing provides more storage and resources with low cost, compared to traditional in-house development environments.